Medijski repertoarji v času navzkrižnih medijskih praks - Oblak Črnič, Tanja (Družboslovne razprave, 2022)
The article explores the relationships between young people’s media choices, technological preferences, and everyday life in connection to their cultural and social characteristics. As such, it describes the conceptual framework of the media repertoires approach and selected methods. Media repertoires are approached from a generational perspective, pointing out the conceptual and empirical challenges of such research. As one of the first attempts to conceptualise media practices at the intersection of family, educational and peer contexts, the article aims to describe the qualitative research design of an empirical study that considered a sample of 67 students aged 12 to 19. The sample is presented through an analysis of its sociodemographic characteristics, while personal media networks help identify the teenagers’ media preferences and their potential cross-connections
Keywords: Digitalne komunikacije; družbene domene; družbeni mediji; everyday life; focus groups; fokusne skupine; komunikacijske prakse; media repertoires; Mediji; medijske skice; medijski repretoarji; mladi; Mladina; personal media networks; social domains; youth